(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article is dedicated to the analysis of the possibilities and prospects of integrating fractal theory in the field of psychology and related scientific areas. It examines various approaches to the application of fractal principles in the study of psychological phenomena, including psychodynamic, social-psychological, sociological, and linguistic perspectives. Special attention is given to the analysis of how fractal theory can enrich traditional approaches, providing new tools for understanding complex patterns of behavior and human interaction with the surrounding world. The article offers a multidisciplinary view on fractal models in social sciences, revealing the potential of fractal theory in expanding the boundaries of understanding the human psyche and sociocultural processes.